Evaluation on Decomposition granularity of Manufacturing Task in Manufacturing Grid - Yong Yin; Chaoyong Zhang; Jihong Wang (Institute of Advanced Engineering and Science, 2013)
Task decomposition is on of the most important activities for manufacturing task planning in Manufacturing Grid. Many achievements in the methods to decompose manufacturing tasks have been obtained. But as for the decomposition granularity, the study and research are rare. Referring to the principle of “strong cohesion and weak coupling” in the software engineering field, the decomposition model of manufacturing task is built up, in which a manufacturing task is decomposed into different subtasks, and each subtask is composed of various processing events. On the basis of the model, the constraint among processing events within the subtasks is analyzed. Then the evaluation index on decomposition granularity of manufacturing task is put forward based on several definitions and evaluation steps for the decomposition granularity of manufacturing task are listed. Finally, examples to illustrate the idea of the paper are given. We hope the work of the paper can promote the study and application for Manufacturing Grid further. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2070